Entrepreneurial Wealth and Employment: Tracing Out the Effects of a Stock Market Crash - RING, MARIUS A. K. (Journal of Finance, 2023)
ABSTRACT Using the dispersion in stock returns during the financial crisis as a source of exogenous variation in the wealth of Norwegian entrepreneurs who held listed stocks, I show that adverse shocks to the wealth of business owners had large effects on their firms' financing, employment, and investment. The effects on investment and employment are driven by young firms, that obtain differentially less bank financing following an owner wealth shock. The effects on employment operate primarily through reduced hiring. My findings highlight that equity‐financing frictions and the procyclicality of entrepreneurial wealth are important channels that can amplify economic shocks.